2020
DOI: 10.1186/s12860-020-00273-2
|View full text |Cite
|
Sign up to set email alerts
|

EphB4/ TNFR2/ERK/MAPK signaling pathway comprises a signaling axis to mediate the positive effect of TNF-α on osteogenic differentiation

Abstract: Background: Low concentrations of tumor necrosis factor-alpha (TNF-α) and its receptor TNFR2 are both reported to promote osteogenic differentiation of osteoblast precursor cells. Moreover, low concentrations of TNF-α upregulate the expression of EphB4. However, the molecular mechanisms underlying TNF-α-induced osteogenic differentiation and the roles of TNFR2 and EphB4 have not been fully elucidated. Results: The ALP activity, as well as the mRNA and protein levels of RUNX2, BSP, EphB4 and TNFR2, was signific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…As mentioned in 2.2, the Runx2 level is potentially associated with TNFR2 signaling. ( Zhang et al, 2020 ) MSCs: mesenchymal stem cells; CFU-M: Colony forming unit M, namely monoblast. M-CSF: macrophage colony-stimulating factor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned in 2.2, the Runx2 level is potentially associated with TNFR2 signaling. ( Zhang et al, 2020 ) MSCs: mesenchymal stem cells; CFU-M: Colony forming unit M, namely monoblast. M-CSF: macrophage colony-stimulating factor.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Y Zhang et al led a study on EphB4/TNFR2/ERK/MAPK signaling. ( Zhang et al, 2020 ). Previous studies showed that low concentrations of TNFα and TNFR2 could upregulate EphB4 expression and promote osteogenic differentiation of osteoblast precursor cells.…”
Section: Tnfr1 Tnfr2 and Rank/rankl/osteoprotegerin In Bone Fracture ...mentioning
confidence: 99%
See 2 more Smart Citations
“…These opposing experimental results may be due to the dose-dependent effect of TNF-α on osteoblasts. It has been shown that low concentrations (0.5 ng/mL) of TNF-α significantly promoted osteoblastic differentiation of osteoblasts in vitro [ 163 ]. It increased the expression of osteoblast Runx2 and BSP activity, and the expression of TNFR2, the receptor of TNF-α, was elevated.…”
Section: Effect Of the Macrophage–osteoblast Axis On Bone Homeostasismentioning
confidence: 99%